Microwave circuits enabling 5G/6G communication - Dwivedi S. (My University, 2025)
There is growing demand for 5G as well as 6G technologies as per user's requirements and enhanced applications. As low latency and high data rates are key findings of 5G, in same way more improved bandwidth, maximum data enabled rate, and many new applications are basic achievable things from 6G systems. There are several types of microwave circuits used for such high frequency. RF/microwave circuits include antennas, filters, power amplifiers, phase shifters, power dividers, mixers, and multiplexers. Here, microwave antennas have been discussed under the microwave circuits. In the last few years, as per economic and social development which is greatly influenced by the advancements in mobile communication and technology, 5G technology has emerged as an important of the future 2020 generation which is already in use. After the development of fifth- generation technologies, researchers, scientists, and engineers are looking for wide bandwidth which should improve wireless systems and devices to provide better services and faster experience. Also, the development of 5G wireless network technology is the response to the crucial factors that lead to this demand because of its ability to provide extremely fast internet speed, high bandwidth, high performance, reduced latency, and high reliability and better gain. In this chapter, we will review the recent design with advancement in 5G antennas for beyond 5G applications and also we will give a few designs of antennae for 6G applications. © 2025 by IGI Global Scientific Publishing. All rights reserved.